(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The purpose of this research is to investigate the variables impact customers’ propensity to utilise banking chatbots. Customer knowledge of the service, their perception of the privacy risk, and the technological acceptance model were the pillars upon which the measurement framework & hypotheses were built. There are 287 people in the sample, and 24 percent of them have used a chatbot for banking at some point. After a measurement model verified that the measure’s items were accurate, PLS-SEM was used to evaluate the hypotheses. Research indicates that compatibility & perceived usefulness are the two most critical aspects of banking chatbot adoption. Knowing about the service influences how easy it is to utilise, how worried people are about their privacy, and how likely they are to use banking chatbots because of how valuable they think they are. Not only that, but one’s impression of the product’s utility affects their impression of how easy it is to use, and vice versa for compatibility. Neither the perceived privacy risk nor the perceived ease of use influences the propensity to utilise.